STRATEGI GURU DALAM MENUMBUHKAN ETIKA SOPAN SANTUN SISWA MELALUI MUATAN PPKN DI KELAS IV SDN TEGALGEDE 3 KARANGANYAR - Wachid Pratomo; Dwi Wijayanti (Universitas Sarjanawiyata Tamansiswa, 2022)
Education is a process of changing the attitudes and behavior of individuals or groups through learning, teaching, and training efforts to achieve certain goals. This study aims to describe the teachers’ strategy, supporting factors, inhibiting factors, and solutions to overcome obstacles in growing students' ethical manners through Civic education content for Class IV SDN Tegalgede 3 Karanganyar. This research method used a qualitative descriptive method with data sources: the school principal, fourth-grade teachers, and fourth-grade students. Data collection techniques used were observation, interviews, and documentation. The analysis technique was by reducing the data, presenting the data, and concluding the data. This study indicated that: (1) The teachers’ strategy was to provide habituation of good behavior when learning Civics. (2) Supporting factors for fostering student ethics were class teachers and students (3) Inhibiting factors came from students and class teachers. (4) The solution to overcome the obstacles was that the teacher provided strict rules. Teachers created comfortable and safe learning conditions for students.